2022
DOI: 10.14797/mdcvj.1092
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Critical Care: The Evolution of a Novel Subspecialty

Abstract: Driven by evolving patient demographics and disease burdens over the past several decades, the demands placed on the cardiac intensive care unit have steadily increased. Originally born out of the need for post-infarction arrhythmia monitoring, the modern cardiac intensive care space is now encountering progressively more complex patients with multisystem organ failure and, increasingly, complex mechanical circulatory support. This complexity has fueled a demand for specifically trained cardiac intensivists, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In a randomized trial, WCD significantly reduced total mortality but not arrhythmic mortality in the intention-to-treat analysis [11]. Further per protocol and as-treated analyses showed that WCD significantly reduced total mortality, as well as arrhythmic and non-arrhythmic death [12,[15][16][17][18][19]22]. Importantly, several large observational studies unanimously showed improved WCD compliance compared to the randomized trial, suggesting that the results of the per protocol and as-treated analyses are closer to real-life clinical practice [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized trial, WCD significantly reduced total mortality but not arrhythmic mortality in the intention-to-treat analysis [11]. Further per protocol and as-treated analyses showed that WCD significantly reduced total mortality, as well as arrhythmic and non-arrhythmic death [12,[15][16][17][18][19]22]. Importantly, several large observational studies unanimously showed improved WCD compliance compared to the randomized trial, suggesting that the results of the per protocol and as-treated analyses are closer to real-life clinical practice [23].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the clinical presentation of patients with acute coronary syndrome (ACS), these patients can be managed in coronary intensive care units (ACCU) or an intensive care unit (ICU) [18,19]. Furthermore, in patients at high risk for SCD, the WCD is prescribed in the hospital prior to discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the approach adopted by the American Boards of Anesthesiology, Internal Medicine, Pediatrics and Surgery in the 1980s mandating distinct CCM fellowship pathways and examinations-generated multiple subspecialty adjectives to describe an intensivist (1, 118). Third, the variability in intensivist nomenclature has also been amplified in the last decades with the addition of neurological critical care and emergency medicine critical care training tracks and board certifications (118, 119), subspecialty intensivist tracks (cardiology intensivists (120–122), critical care nephrologists (123, 124), cardiac anesthesiology intensivists (125)), and expanded surgical critical care training that now includes surgery, anesthesiology, and emergency medicine applicants (126, 127). Finally, the diversity of Intensivist nomenclature may also reflect the increasing number of specialty ICUs where intensivists primarily practice in large academic medical centers (1, 117).…”
Section: Discussionmentioning
confidence: 99%
“…Despite increasing cardiovascular morbidity and complication rates, overall mortality was not found to be significantly higher in the 2017 cohort compared to 2007. This provides an opportunity to shed more light on the fact that in the past decade, the intensive management of cardiovascular issues has changed[ 23 , 24 ]. With improved cardiac critical care management, including the implementation of evidence-based protocols[ 25 ], rapid recognition of life-threatening conditions, and attention to patient safety, we have been able to reduce cardiovascular mortality in the past decade[ 24 ].…”
Section: Discussionmentioning
confidence: 99%